Design and test of powerful air-assisted sprayer for high stalk crops - Miao, Youyi; Chen, Xiao; Gong, Yan; Liu, Dejiang; Chen, Jian; Wang, Guo; Zhang, Xiao (Frontiers in Plant Science, 2023)
The canopies of high stalk crops, such as maize, intersect the rows at the later stages of growth, making conventional sprayers unable to enter the field for spraying. Air-assisted sprayers are often used to improve the deposition of droplets inside the canopy. In this study, the sprayer structure, the air-assisted system, and the spraying system were designed. The air-assisted conveyor system characteristics were numerically analyzed, and the wind-field distribution was tested. The wind-field distribution results showed that the near-ground wind speed exceeded 5 m s-1 in the sampling interval from 10 to 35 metres. The wind field covered a concentrated spatial area with a downward pressure trend, resulting in better drift resistance and penetration. Field tests for droplet distribution were conducted at three maize heights to verify the powerful air-assisted sprayer's technical performance and working quality. The test results showed that the droplet deposition and coverage decreased gradually along the range direction, and the top layer had the highest deposition and coverage across the canopy. The upper canopy of 0 to 12 metres range demonstrated a greater extent of coverage and deposition. The peak deposition area expanded from 9 to 33 metres in the lower canopy, with an average value of 3.77 μg cm-2. The droplet coverage within the 30 to 60 metres range only amounted to 15% to 18% of the total coverage.